المقارنة بين امرئ القيس وأبى نواس فى تنظيم الشعر - Muhammad Nadir (Jurnal Al-Maqoyis, 2014)
This essay will discuss the comparison between Umru’ul Qais and Abu Nuwwas in composing their Arabic poems. These two leaders in Arabic poetry had a significant role and influence in determining the Arabic literature especially in the field of poetry. The far different distance of the era of these two leaders made a dynamic stage in performing poetry in Arabic. The main argument of this paper focuses on the topics and methods they used in composing a poem. The first part of this essay deals with the biography of Umru’ulQais and Abu Nuwwas and the milieu that influenced their characters in poetry. The second part addresses the different in the styles and rhythms in saying poetry. As a reformer, Abu Nuwwascameoverhaulingthe old style of poetries and make them free from the rigid rhymes. The last part of the essay speaks about the main topics of the poetry of both Umru’ulQais and Abu Nuwwas.